2018
DOI: 10.1111/gcb.13923
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the direct and indirect effects of climate on plant litter decomposition: Accounting for stress‐induced modifications in plant chemistry

Abstract: Decomposition of plant litter is a fundamental ecosystem process that can act as a feedback to climate change by simultaneously influencing both the productivity of ecosystems and the flux of carbon dioxide from the soil. The influence of climate on decomposition from a postsenescence perspective is relatively well known; in particular, climate is known to regulate the rate of litter decomposition via its direct influence on the reaction kinetics and microbial physiology on processes downstream of tissue senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 251 publications
(411 reference statements)
6
80
1
Order By: Relevance
“…The relationship between biodiversity and ecosystem function is one of the most fundamental questions asked by ecologist. Despite this, few field studies have explicitly evaluated how global changes alter the dynamics between plant community composition and carbon cycle processes (Smith et al, ; Suseela & Tharayil, ; Yao, Piao, & Wang, ). In this study, our results revealed that the variation of R h was best jointly explained by the changes in plant species richness and litter degradability.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between biodiversity and ecosystem function is one of the most fundamental questions asked by ecologist. Despite this, few field studies have explicitly evaluated how global changes alter the dynamics between plant community composition and carbon cycle processes (Smith et al, ; Suseela & Tharayil, ; Yao, Piao, & Wang, ). In this study, our results revealed that the variation of R h was best jointly explained by the changes in plant species richness and litter degradability.…”
Section: Discussionmentioning
confidence: 99%
“…The climatic stressors that modify the chemical composition of plant tissues have been recently reviewed by Suseela and Tharayil (). In particular, the authors stated that the response of plants to global change effects ( viz .…”
Section: Effects Of Global Change In the Hydric Thermal And Mechanimentioning
confidence: 99%
“…Overall, the decomposition of plant‐derived organic matter has been the focus of attention lately as shown by the number of recent reviews covering topics from plant‐soil feedbacks, abiotic and biotic drivers, and the consequences of climate on these drivers, but also the impact of plant species on litter degradation . Evidence from previous studies suggests that the complexation of proteins by tannins conserves N derived from litter with consequences for plant N acquisition via resulting in organic over mineral N dominated pathways .…”
Section: Effects Of Climate Change On Plants Secondary Metabolites – mentioning
confidence: 99%